Artificial intelligence and soft computing. 17th International Conference, ICAISC 2018, Zakopane, Poland, June 3-7, 2018, Proceedings /: 17th International Conference, ICAISC 2018, Zakopane, Poland, June 3-7, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available